Pengaruh Struktur Kepemilikan, Komite Audit, Ukuran KAP, Ukuran Dewan Komisaris dan Leverage Terhadap Biaya Keagenan Pada Perusahaan Manufaktur (Industri Barang Konsumsi) Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014 - Devvy Noveliza (Program Studi Manajemen, Fakultas Ekonomi, IBI-K57, 2020)
The purpose of studi is to empirically examine the influence of the institutional ownership, the managerial ownership, the audit committee, the audit firm size, the size of the board commissioners and of the leverage towards the costs of agency. The 37 manufacturing companies (consumer goods industry) which are listed in the Indonesian Stock Exchange (BEI) in 2010-2014 become the population of this study whilst the 27of the 37 manufacturing companies listed in the Indonesia Stock Exchange in the similar years are selected to be the samples. Purposive sampling is used in this study. The result of this study shows that both the institutional ownership and the audit firm size have a significant effect on agency costs but the managerial ownership, the audit committee, the size of board commissioners and the leverage do not have a significant effect on the agency cost. The institutional ownership, the managerial ownership, the audit committee, the audit firm size, the size of board commissioners and the leverage jointly have a significant effect on agency costs.